The Impact of Non-Cash Payment Systems on Inflation in Indonesia - Akbar Lufi Zulfikar; Selly Swandari; Swadia Gandhi Mahardika; Imelda Veronica Gea (Yayasan Inovasi Kemajuan Intelektual, 2026)
This study investigates the impact of non-cash payment systems on inflation in Indonesia, focusing on three major instruments: ATM cards, credit cards, and electronic money (e-money). The rapid development of digital payment technologies has transformed consumer behavior and the circulation of money, potentially influencing the country’s inflation dynamics. Using a quantitative research approach and multiple linear regression analysis, this study examines monthly data from 2022 to 2024 to assess how different non-cash transactions affect inflation. The empirical findings reveal that ATM card transactions have a positive and statistically significant effect on inflation, indicating that higher ATM transaction volumes are associated with increased consumer spending. Conversely, credit card transactions demonstrate a negative but significant effect, suggesting that deferred payments may moderate inflationary pressures. Meanwhile, e-money transactions have a negative yet insignificant effect, implying limited influence given their lower transaction volume compared to other instruments. Overall, the results highlight that the impact of non-cash payment systems on inflation varies across payment types and their intensity of use, providing valuable insights for policymakers in managing monetary stability amid the growing digitalization of financial systems.